2000
DOI: 10.1164/ajrccm.162.3.9912067
|View full text |Cite
|
Sign up to set email alerts
|

Genioglossal But Not Palatal Muscle Activity Relates Closely to Pharyngeal Pressure

Abstract: The stimuli controlling pharyngeal dilator muscles are poorly defined. Local mechanoreceptors are a leading possibility. To address this, we assessed the relationship between two dilator muscle electromyograms (EMGs, i.e., genioglossus [GG-an inspiratory phasic muscle], tensor palatini [TP-a tonically active muscle]) and potential stimuli (i.e., epiglottic pressure [Pepi], airflow [V], and pharyngeal resistance [Rpha]). Fifteen normal subjects were studied, during wakefulness and stable non-rapid eye movement … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
84
0
5

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 120 publications
(97 citation statements)
references
References 22 publications
8
84
0
5
Order By: Relevance
“…It can influence both the structure [7] and function [8] of skeletal muscles. However, to the best of the authors9 knowledge, its effects upon the upper airway muscles have not been directly addressed by previous studies in the field [5,[9][10][11]. A retrospective analysis of the current authors9 data [5] suggested that the function of the GG in obese and nonobese patients with OSAS may be different.…”
mentioning
confidence: 74%
“…It can influence both the structure [7] and function [8] of skeletal muscles. However, to the best of the authors9 knowledge, its effects upon the upper airway muscles have not been directly addressed by previous studies in the field [5,[9][10][11]. A retrospective analysis of the current authors9 data [5] suggested that the function of the GG in obese and nonobese patients with OSAS may be different.…”
mentioning
confidence: 74%
“…This defect in neuromuscular control was independent of age, obesity, and sex (86), and may be caused by sleep-related reductions in dilator activity during sleep compared with wakefulness (87,88) or by a loss of compensatory responses during sleep (87)(88)(89)(90)(91)(92)(93)(94)(95)(96)(97)(98)(99). Thus, current evidence indicates that sleep apnea is associated with fundamental disturbances in upper airway mechanical (68,100,101) and neuromuscular control (80,(102)(103)(104)(105)(106)) (see Figure 1, left), and suggests that a combined defect is required to produce sleep apnea (86). Nevertheless, the impact of obesity on upper airway mechanical and neural properties has not been elucidated.…”
Section: Obesity and Upper Airway Neuromechanical Control Modeling Upmentioning
confidence: 95%
“…During sleep, the phasic activation increases slowly when upper airway pressure becomes more negative due to a substantial reduction but not complete loss of reflex mechanisms. 27 Using our sleeping upper airway model, we assessed pharyngeal collapsibility (ie, Pcrit) during normal sleep and following three anatomic manipulations: mandibular advancement, uvulopalatopharyngoplasty (UPPP), and palatal stiffening. In our model, we simulated mandibular advancement by stretching the muscle to reach a 1-cm anterior mandibular displacement.…”
Section: Methodsmentioning
confidence: 99%